FACTORS INFLUENCING PREGNANT WOMEN’S COMPLIANCE WITH ANC EXAMINATION: A SCOPING REVIEW - Shalma, Avriana Faiza; Nency Agustia (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
The leading causes of maternal death are hemorrhage, preeclampsia, infection, and childbirth complications. Non-compliance with antenatal care (ANC) visits is a serious problem because it directly impacts the ability of healthcare workers to detect obstetric complications early. In Indonesia, pregnant women are still found to be late or not attending ANC regularly, preventing potential complications from being managed promptly and appropriately. The purpose of this study was to determine the factors associated with pregnant women's compliance with ANC examinations. The method used was a scoping review. Using a framework with the steps of identifying the review focus, developing the review focus and search strategy, identifying relevant studies, mapping data using PRISMA, extracting by compiling, summarizing, and reporting the results and discussion. The results of the scoping review after the PRISMA process obtained 10 articles (the initial number of articles was 2,811) with grade A (critical appraisal) selected using quantitative methods. The themes identified were individual factors, including knowledge, age, attitudes, education, employment status, and parity. Support factors included husband's support. Health service factors included access or distance, and midwives. By understanding these factors, policymakers and health practitioners can develop targeted interventions to encourage pregnant women to attend regular ANC check-ups, ultimately maximizing maternal and child health